Evaluation of the interface of eucalyptus specimens welded by rotary friction - Costa Viana, Ana Carolina; Dias de Moraes, Poliana; Weingaertner, Walter Lindolfo (Maderas. Ciencia y Tecnología, 2023)
Rotary friction welding produces joints by inserting wood dowels, with a specific rotation and feed rate, into pre-drilled holes made in wood substrates. Studies on the welding of fast-growing eucalypts from Brazilian planted forests are recent. Therefore, this research aimed to evaluate the macro and microstructural and thermochemical changes at the dowel/substrate interface of eucalypts welded joints from Brazilian planted forests and to determine the mechanical strength of two-piece eucalypts welded joints. Specimens formed by eucalypts dowels and substrates were produced. Subsequently, visual evaluation and scanning electron microscopy, attenuated total reflectance-Fourier transform infrared spectroscopy, X-ray diffraction, thermogravimetric, differential scanning calorimetry and tensile tests were performed. The results reveal that the rotary friction welding parameters adopted contribute to the densification of the welded interface and the formation of a structure responsible for joining the dowel and the substrate, providing mechanical strength to the joint. The cellulose crystallinity index and the apparent crystallite size of the eucalypts welded sample increase due to thermal degradation of amorphous components. The rupture of the welded joints is ductile and their average strength is 2,1 MPa. Welded joints of fast-growing eucalypts, from Brazilian planted forests, are suitable when the rotary friction welding parameters are similar to those used for eucalypts woods from Australian forests.